Peeling the onion top-down: Language policy in Serbia between power and myth - Stanković, Branimir; Stefanović, Marija (Aegean Working Papers in Ethnographic Linguistics, 2019)
This paper considers the issue of language policy and planning in Serbia, as managed by the main competent institution, the Serbian Language Standardization Committee, a trans-state, national institution dealing with vital issues of language policy and planning. Specifically, assuming a Bourdieusian perspective, it investigates the ideology behind the Committee’s policies, grounded in a series of language myths, and the way these policies influence professionals and everyday language users. The effects of a rigid, strict educational system and a standard language culture by educators are shown in detail focusing on the Torlak dialect in Southern Serbia. The Serbian case reveals a constant promotion of censorship and a heightened understanding of the benefits of self-censorship in the language market. This can be seen in the pressure exerted on certain speakers and the threat their mother tongue represents for their status in the labor market.